Areas under peripheral pulse waves: a potential marker of atherosclerotic changes. (26th February 2018) - Peltokangas, Mikko; Verho, Jarmo; Mattila, Ville M; Romsi, Pekka; Vehkaoja, Antti; Lekkala, Jukka; Oksala, Niku
Abstract: Objective : In this study, we propose a method for finding atherosclerotic changes based on the ratios of areas under peripheral arterial pulse wave (PW) contours and analyze its performance. Approach : The PW signals were recorded with force sensors and photoplethysmographic sensors from ankle, wrist, cubital fossa, index finger and second toe from 30 atherosclerotic patients and 52 control subjects. In addition, the day-to-day repeatability of the method was studied with 10 test subjects examined on three different days. The ratios of areas under the PWs were computed and the results were evaluated by means of receiver operating characteristic (ROC) analysis, intra-class correlation (ICC) coefficient and multiple linear regression analysis. Main results : Areas under ROC curves of 0.802–0.906 were found for different area ratios having statistically significant differences between the atheroslerotic group and control groups. ICCs over 0.80 were found widely for the beat-by-beat analyzed data and over 0.95 for the data based on the averages over different numbers of PWs. Multiple linear regression analysis showed linear dependence between the area ratios and age and the diagnosis of atherosclerosis. Significance : Our findings may facilitate development of novel diagnostic approaches and preventive strategies against cardiovascular disorders. However, further studies are needed to confirm the results. The presented study demonstrates the potential of arterial PW analysis in finding vascular abnormalities.